A microencapsulated feed additive containing organic acids and botanicals has a distinct effect on proliferative and metabolic related signaling in the jejunum and ileum of broiler chickens - Johnson, Casey N.; Arsenault, Ryan J.; Piva, Andrea; Grilli, Ester; Swaggerty, Christina L. (Frontiers in Physiology, 2023)
Well designed and formulated natural feed additives have the potential to provide many of the growth promoting and disease mitigating characteristics of in-feed antibiotics. The most advanced of these in-feed alternatives to antibiotics are designed to have a targeted effect on specific areas of the gut and have ingredients that elicit a variety of positive effects on the host. Here, we describe the mechanism of action of a microencapsulated feed additive containing organic acids and botanicals on the jejunum and ileum of broiler chickens. Chicken-specific kinome peptide array analysis was conducted on jejunum and ileum tissue samples from broiler chickens fed either a diet containing a microencapsulated blend of organic acids and botanicals or a non-supplemented diet (control). Detailed analysis of peptides representing individual kinase target sites revealed that in the ileum there was a broad increase in the signal transduction pathways centering on activation of HIF-1α, AMPK, mTOR, PI3K-Akt and NFκB. These signaling responses were largely decreased in the jejunum relative to control birds. Gene expression analysis is in agreement with the kinome data showing strong immune gene expression in the ileum and reduced expression in the jejunum. The microencapsulated blend of organic acids and botanicals elicit a more anti-inflammatory phenotype and reduced signaling in the jejunum while resulting in enhanced immunometabolic responses in the ileum.